Curtailing smartphone use: a field experiment evaluating two interventions. Issue 16 (10th December 2022) - Ochs, Carli; Sauer, Juergen
ABSTRACT: This field experiment aimed to address the issue of problematic smartphone usage (PSU) by examining the effectiveness of two frequently advised techniques to deal with PSU: moving problematic applications to a different page of the phone and changing the phone into greyscale. For one week, 97 student participants used their smartphone under one of the following three conditions: move app, greyscale, or control condition. Compared to the week before the intervention, participants significantly reduced their objective smartphone usage, but their self-reported PSU increased. These effects also emerged in the control group, which might have been due to heightened awareness of the participants of their smartphone usage. A major implication of the study is the need of using multiple outcome measures to understand the complex relationship between perceptions and behaviour. This study could be used as a blueprint for future research examining the effectiveness of interventions in the field of PSU.